Anti-TNF antibody treatment improves glucocorticoid induced insulin-like growth factor 1 (IGF1) resistance without influencing myoglobin and IGF1 binding proteins 1 and 3. Issue 3 (3rd August 2005) - Sarzi-Puttini, P; Atzeni, F; Schölmerich, J; Cutolo, M; Straub, R H
Abstract : Background: Insulin-like growth factor 1 (IGF1) is an important determinant of muscle mass because it promotes growth and suppresses protein degradation. IGF1 is decreased in rheumatoid arthritis and juvenile idiopathic arthritis because its synthesis is inhibited by inflammation. In parallel, glucocorticoids induce IGF1 resistance and add to muscle degradation. Objective: To investigate the influence of anti-tumour necrosis factor antibody treatment (anti-TNF) with adalimumab on levels of myoglobin (degradation marker) and IGF1 in patients with rheumatoid arthritis with and without prednisolone treatment. Methods: Subcutaneous adalimumab was given to 32 patients with longstanding rheumatoid arthritis (16 with and 16 without prednisolone) in a longitudinal study. IGF1, IGF1 binding protein 1 (IGFBP-1), IGFBP-3, and myoglobin were measured by enzyme linked immunosorbent assay. Results: Rheumatoid patients had normal serum myoglobin. Patients on prednisolone had higher myoglobin than patients not receiving prednisolone, indicating increased muscle degradation. On treatment with anti-TNF, myoglobin levels did not change in either patient group. Serum IGF1 was increased in patients with v without prednisolone, indicating IGF1 resistance (mean (SEM): 221 (23) v 122 (14) μg/l, p<0.001). Adalimumab treatment decreased the raised IGF1 levels in patients with prednisolone, so that after 12 weeks of treatment they reached the level of patients without prednisolone. Serum IGFBP-1 and IGFBP-3 did not differ in the two groups, and anti-TNF did not change these concentrations. Conclusions: Anti-TNF antibody treatment over 12 weeks improved glucocorticoid induced IGF1 resistance without influencing myoglobin and IGF1 binding proteins. Thus, in rheumatoid patients on glucocorticoids with generally decreased muscle mass anti-TNF treatment with adalimumab has favourable effects.